An Empirical Study of Tax and Inflation Effects Towards Dividend Policy in Indonesian Listed Companies - Hardiyanti, Nurul (2011)
Firm’s dividend policy is one of the main considerations in investment decision-making. Past empirical evidences use proxies of dividend irrelevance theory, agency cost theory, dividend signaling theory, pecking order theory, and free cash flow theory to investigate the determinant of dividend policy. This study extends the prior researches by investigating the effects of tax and inflation towards the dividend policy of listed firms in the Indonesian Stock Exchange from 2000 to 2009. This study applies the Ordinary Least Squares (OLS) method to measure the effects. The findings reveal that both tax and inflation do not significantly affect the dividend policy of all sample Indonesian firms. However, the result comes up differently when those firms are classified into their respective industry sectors. This study documents the evidence that four industry sectors are positively affected by tax, namely Agriculture industry, Consumer Goods industry, Miscellaneous industry, and Property, Real Estate and Building Construction industry. The Mining industry, on the other hand, is negatively affected by tax. Meanwhile, only two industry sectors that are found to be positively affected by inflation, which are Agriculture industry and Basic Industry and Chemical industry.